Getatchew Haile with Melaku Terefe - Roger M. Rundell - Daniel Alemu - Steve Delamarter: Catalogue of the Ethiopic Manuscript Imaging Project, Vol. 1; and Steve Delamarter - Melaku Terefe: Ethiopian Scribal Practice 1: Plates - Bausi, Alessandro (Aethiopica, 2010)
Review